Subcutaneous Fat Necrosis of the Newborn: A Case Report - Soung Hee Kim (대한영상의학회지, 2018)
Subcutaneous fat necrosis (SFN) in newborns is a rare disease that affects infants in the first few weeks after birth. The lesion involves the back, buttocks, thighs, arms, and cheeks and it appears as a subcutaneous nodule in firm, well-defined, purplered manifestation. It is a self-limited disorder and follows an uncomplicated course, but serious complications may occur such as thrombocytopenia, hypoglycemia, hypertriglyceridemia, and hypercalcemia. I am reporting a case of ultrasonographic and MR imaging findings of SFN in a 35–day-old girl with hypercalcemia and medullary nephrocalcinosis.